General Approaches to Solving Problems of Analysis and Synthesis of Directional Properties of Antenna Arrays - I. Islamov; E. Humbataliyev (Advanced Electromagnetics, 2022)
The work carried out the calculation and synthesis of antenna arrays used in radio-electronic complexes on unmanned aerial vehicles. The analytical model is designed to find asymptotic estimates of the polarization components of the electric field of the grating in the far zone of the carrier surface; the results obtained with its use are the initial data for constructing a technique for the numerical solution of a boundary value problem for a grating on a carrier surface in the CST MWS electrodynamic simulation environment. The synthesis of gratings with the maximum achievable coefficient of directional action is carried out with the control of radiation patterns at a given set of angles. A two-mirror antenna system has been calculated. It is shown that with an increase in the number of re-reflections taken into account, the convergence of the result for the calculated characteristics of the antenna is observed. To test the proposed method, the same antenna was calculated using the integral equation method. The comparison showed a high degree of agreement between the results obtained by two different methods. The results of the simulation based on a software algorithm designed to quantify the input matching at the input of a multichannel frequency-scanning antenna array power divider are presented. It was found that when performing wide-angle scanning in a relative frequency band of more than a few percent, the disadvantage of the known method for eliminating the normal effect is a sharp deterioration in matching in the lower and upper frequencies of the operating range. A new method is proposed based on an automated iterative process of optimizing the divider geometry, which makes it possible to obtain an acceptable match over the entire operating frequency band. The feasibility of switching from a serial power divider construction scheme to a series-parallel scheme is analyzed for wide-angle scanning in a relative frequency band of about 5%.